2018
DOI: 10.1111/jne.12584
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and quantitative meta‐analysis of the effects of oxytocin on feeding

Abstract: Oxytocin reduces energy intake when administered as a single dose. Oxytocin can inhibit feeding over two- to three-week periods in rodent models. These effects typically do not persist beyond the third week of treatment. The anorexigenic effect of oxytocin is moderated by pregnant status, dose, method of administration, and diet composition. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 79 publications
(119 reference statements)
3
43
0
Order By: Relevance
“…[161][162][163] The anorexigenic effect of oxytocin has been shown to be stronger in diet-induced obese rodents. 161 SNPs of the gene encoding the oxytocin receptor have been shown to be associated with eating disorders including anorexia nervosa and bulimia nervosa. 161 SNPs of the gene encoding the oxytocin receptor have been shown to be associated with eating disorders including anorexia nervosa and bulimia nervosa.…”
Section: Roles Of Oxytocin In the Control Of Food Intakementioning
confidence: 99%
See 2 more Smart Citations
“…[161][162][163] The anorexigenic effect of oxytocin has been shown to be stronger in diet-induced obese rodents. 161 SNPs of the gene encoding the oxytocin receptor have been shown to be associated with eating disorders including anorexia nervosa and bulimia nervosa. 161 SNPs of the gene encoding the oxytocin receptor have been shown to be associated with eating disorders including anorexia nervosa and bulimia nervosa.…”
Section: Roles Of Oxytocin In the Control Of Food Intakementioning
confidence: 99%
“…130,146,159,160 Oxytocin administration has been shown to reduce food intake in laboratory animals and humans. [161][162][163] The anorexigenic effect of oxytocin has been shown to be stronger in diet-induced obese rodents. 164 However, a meta-analysis revealed that the anorexigenic effect of oxytocin administration is not statistically significant in humans.…”
Section: Roles Of Oxytocin In the Control Of Food Intakementioning
confidence: 99%
See 1 more Smart Citation
“…The oxytocin (OT) system has been a promising research area in translational neuroscience over the past decade (1,2). Robust evidence from studies in preclinical models has demonstrated the importance of the central OT system in the development (3) and regulation of complex social behaviours (4,5), the modulation of pain processing (6), feeding behaviour (7) and neuroinflammation after brain ischemia (8). Harnessing the central OT system has been identified as a potential strategy for the development of targeted pharmacological interventions to help to improve outcome in several conditions for which efficacious treatments do not currently exist (e.g autism spectrum disorder (9), schizophrenia (10), migraine (11), stroke (8), obesity (12), Prader-Willi (13)).…”
mentioning
confidence: 99%
“…One such potential treatment is intranasal oxytocin (OT) [27][28][29] . Support for the implication of OT in binge eating comes from animal 30 and human studies 31,32 demonstrating that OT suppresses eating, including hedonic eating in men 33 . Some small clinical studies have also shown that intranasal OT (40IU) reduces caloric intake 34 and decreases vigilance towards angry faces 35 in women with BN.…”
Section: Introductionmentioning
confidence: 99%